Genipin-Crosslinking Effects on Biomatrix Development for Cutaneous Wound Healing: A Concise Review - Utami Nike, Dewi; Md Fadilah, Nur Izzah; Sallehuddin, Nusaibah; Nor Azlan, Ahmad Yasser Hamdi; Imran, Farrah Hani; Maarof, Manira; Fauzi, Mh Busra (Frontiers in Bioengineering and Biotechnology, 2022)
Split skin graft (SSG), as a standard gold treatment for wound healing, has numerous limitations such as lack of fresh skin to be applied, tedious process, severe scarring and keloid formation followed by higher risks of infection. Thus, there is a gap in producing polymeric scaffolds as an alternative for wound care. Bioscaffold is the main component in tissue engineering technology that provides three-dimensional porous three-dimensional (3D) microarchitecture for cells to survive. Upon skin tissue reconstruction, the 3D-porous structure ensures sufficient nutrients and gaseous diffusion and cell penetration that improves cell proliferation and vascularization for tissue regeneration. Hence, it is highly considered a promising candidate for various skin wound healing applications. To date, natural-based crosslinking agents have been extensively used to tailor the physicochemical and mechanical properties of the skin biomatrix. Genipin (GNP) is preferable to other plant-based crosslinkers due to its biological activities, such as antiinflammatory and antioxidant, which are key players to boost skin wound healing. Besides, it has shown a non-cytotoxic effect and biocompatible towards human skin cells. This review validated the effects of GNP in biomatrix fabrication for skin wound healing from the last five years of established research articles and stipulated the biomaterials development-scale point of view. Lastly, the possible role of GNP in skin wound healing cascade is also discussed. Through the literature output, it can be concluded that GNP has capability to increase the stability of biomatrix and maintain the skin cells viability, which will contribute to accelerating wound healing.